Vending machine purchasing experience among students in the university’s residential college / Mohamad Naqiuddin Md Mansor …[et al.] - Md Mansor, Mohamad Naqiuddin; Mohd Rashid, Norhidayah; Ma’amor, Hairunnisa; Badrolhisam, Nur Idayu; Abdul Aziz, Nor Intan Shamimi (Faculty of Business and Management and UiTM Press Universiti Teknologi MARA, Malaysia, 2018)
University colleges provide cafeteria for student living on campus to purchase foods. These cafeteria open on daily basis, located in separate building and usually within a walking distance from college. A college cafeteria system often has a virtual monopoly on the students due to an isolated location and less competition for on-campus food. There is situation where students must wait for a long time to purchase pre-cooked or ordered foods. The situation will become worse when students are hungry at night and the cafeteria is already closed. In addition most of the cafeterias are closed during semester break since only few students stay at the college. Alternatively, purchasing foods via vending machines are adaptable and acceptable since it operates twenty-four hours seven days a week. Vending machine can provide variety of foods and drinks with affordable price range. This study aims to investigate the purchasing experience among university’s residential college students by using vending machine. The result will help vending machine operators develop and customize their own machines to better serve the customers’ needs.